2018
DOI: 10.1158/0008-5472.can-17-1624
|View full text |Cite
|
Sign up to set email alerts
|

LPA Induces Metabolic Reprogramming in Ovarian Cancer via a Pseudohypoxic Response

Abstract: Although hypoxia has been shown to reprogram cancer cells toward glycolytic shift, the identity of extrinsic stimuli that induce metabolic reprogramming independent of hypoxia, especially in ovarian cancer, is largely unknown. In this study, we use patient-derived ovarian cancer cells and high-grade serous ovarian cancer cell lines to demonstrate that lysophosphatidic acid (LPA), a lipid growth factor and GPCR ligand whose levels are substantially increased in ovarian cancer patients, triggers glycolytic shift… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 45 publications
1
65
0
Order By: Relevance
“…NSD2-driven tamoxifen-resistant cancers exhibit an enhanced PPP activity, elevated NADPH production and reduced ROS levels. For example, treatment of ovarian cancer xenografted mice with the HK2 inhibitor 3-bromopyruvate attenuates tumor growth and confers a survival advantage (53).…”
Section: Glucose Breakdown Through Glycolysis Influencing Pppmentioning
confidence: 99%
“…NSD2-driven tamoxifen-resistant cancers exhibit an enhanced PPP activity, elevated NADPH production and reduced ROS levels. For example, treatment of ovarian cancer xenografted mice with the HK2 inhibitor 3-bromopyruvate attenuates tumor growth and confers a survival advantage (53).…”
Section: Glucose Breakdown Through Glycolysis Influencing Pppmentioning
confidence: 99%
“…Ha et al found that the LPA-LPAR-Gαi2 axis can induce pseudo hypoxic response through the Rac-NOXROS-HIF1α pathway, which ultimately leaded to metabolic reprogramming of ovarian cancer cells. This conclusion was verified by establishing two independent mouse models of ovarian cancer cell line xenograft (CDX) [58]. PI3K/Akt pathway is critical in the process of ovarian cancer.…”
Section: Lpar and Ovarian Cancermentioning
confidence: 73%
“…In this case, the modular expression of different LPA receptors after differential activation hints a complex role of LPA signaling in the homeostasis of macrophages during the disease and suggests that modulating the expression or saturating the activation of one or the other one could be a mechanism of trans-differentiation of human macrophages. Although this aspect requires further study, the fact that LPA1 is related to glycolysis (7,16,33) (main source of energy for pro-inflammatory polarized macrophages) and PPARƔ induces oxidative phosphorylation (35), and that these two metabolic processes are central in pro-and anti-inflammatory macrophage activation respectively (13), suggests that the modulation of these LPA receptors could have major implications in the macrophage physiology and activation.…”
Section: Discussionmentioning
confidence: 99%